Peningkatan Disiplin Kehadiran Mengajar Guru di Kelas Melalui Keteladanan Kepala Sekolah di SDN Aceh Besar - Rahmiati, Rahmiati; Akmaluddin, Akmaluddin; Rahmattullah, Rahmattullah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study was to determine the example of the principal, teacher discipline and the principal's contribution in improving teacher discipline at SD Keci Aneuk Bate. This research method uses qualitative methods. Data collection through direct observation and interviews with resource persons. Data analysis techniques through data reduction, data presentation, and conclusions. The results showed that the principal's attendance at SD Aneuk Bate followed the rules of timely arrival and on time to leave even though it was outside the applicable time. SD Aneuk Bate is very wise in action, able to solve problems in school, confident in practicing, simple in character, but respected by his subordinates. The Principal of SD Aneuk Bate is very concerned about the problems faced by teachers and teaching staff and the Principal of SD Aneuk Bate is also very dedicated and responsible as a leader in carrying out his duties. The discipline of teachers at SD Aneuk Bate is well carried out in terms of compliance with laws and regulations, punctuality, and firm character. This is demonstrated by compliance and enforcement of regulations that can make farmers eligible. The principal's example in improving teacher discipline is well carried out so that he can be an example for his subordinates